On the efficient method of solving ill-posed problems by adaptive discretization - Solodky, S.G.; Volynets, E.A. (Інститут математики НАН України, 2009)
To solve ill-posed problems Ax = f is used the Fakeev-Lardy regularization, using an adaptive discretization strategy. It is shown that for some classes of finitely smoothing operators proposed algorithm achieves the optimal order of accuracy and is more economical in the sense of amount of discrete information then standard methods